Visualization of two-phase flow in metallic pipes using neutron radiographic technique - Luiz , Leandro da Conceição; Crispim, Verginia Reis; Ferreira , Francisco José (Physicae, 2010)
The study of two-phase flow is a matter of great interest both for the engineering and oil industries. The production of oil and natural gas involves the transportation of fluids in their liquid and gaseous states, respectively, to the processing plant for refinement. The forecasting of two-phase flow in oil pipes is of the utmost important yet an extremely difficult task. With the development of the Electronic Imaging System, installed in J-9 irradiation channel of the IEN/CNEN Argonauta Reactor, it is possible to visualize the different types of two phase air-water flows in small-diameter metallic pipes. After developing the captured image the liquid-gas drift flux correlation as well as the void fraction in relation to the injected air outflow for a fixed water outflow can be obtained.